Dose- and time-dependent effects of collagenase clostridium histolyticum injection on transverse carpal ligament elastic modulus and thickness in vitro - Jocelyn L. Hawk; Sohail R. Daulat; David S. Margolis; Zong-Ming Li (PLoS ONE, 2022)
A potential treatment for carpal tunnel syndrome is to biochemically alter the mechanical properties of the transverse carpal ligament (TCL) through Collagenase Clostridium Histolyticum (CCH) injection. The purpose of this study was to determine the time- and dose-dependent effects of CCH injection on TCL elastic modulus and thickness. Nine TCLs were dissected from cadaveric hands for this study. CCH doses of 50U, 100U, 150U, 200U, and 250U were injected into five points on the TCL, respectively. B-mode and shear wave elastography images were taken of each injection point using robot-assisted ultrasound imaging immediately after injection, as well as 2, 4, 6, 8, and 24 hours after injection. TCL thickness and mean shear wave speed were measured for each CCH dose at each time point. CCH doses of 200U and 250U decreased shear wave speed by 18.70% and 30.01% (p<0.05), respectively, after 24 hours. CCH doses of 150U, 200U, and 250U decreased TCL thickness by 7.28%, 10.97%, and 14.92%, respectively, after 24 hours (p<0.05). Our findings suggest that CCH injection may be effective in degrading TCL tissue, with higher doses of CCH resulting in greater tissue degradation up to 24 hours after injection.